Rights and redemption history, law and indigenous people - Curthoys, Ann (University of New South Wales Press Ltd, 2008)
"Aboriginal people have been able to use the courts to try to seek redress, particularly when political options have been limited. To do this they have had to use historical arguments, and as such history and historians have had to enter the courtroom. This highly original book brings together one of Australia's leading historians with two younger legal scholars to examine the ways in which history and the law have interacted in Australia. Far from being an abstract discussion, the book examines hundreds of federal court cases, interviewing judges, litigants, claimants and historians."--Provided by publisher.